Corrosão em meio aquoso, a altas temperaturas e a fragilização do aço em refinarias de petróleo: mecanismos e mitigação - Paulo Pio Alvisi (2007)
This work concern with corrosive process and the ones associated to the embrittlement of steel tipically founded in the petroleum refinery equipment as well as the alternatives used to mitigate it. The corrosive process found inatmospheric and vaccum distillation, in units of fluid catalytic cracking with gas recovery and DEA treatment, hydrotreating including hydrogen production, and delayed coking units are account. The remotion of hydrolysable Mg and Ca chlorides by crude desaltingis the most important action done in the sense of decrease aqueous corrosion in distillation overhead systems and fouling in heat exchanger, coke in process furnaces and reduce salt acid formation in hydrotreating units. For instance, in distillation,the equipment heated to temperature above about 250ºC can suffer sulfidation and naphtenic acid attack. In units of fluid catalytic cracking, the existence of temperatures near of 700ºC, the presence of compound such as CO and CO2, the flow of erosive materials (catalyst) can cause creep, embrittlement microstructural reactions such as grafitization, sigmatization and carbonization, besides erosion. In gas recovery units, is usual the steel contact with electrolyte with ions such as HS-, NH4+ and CN-, get possible the hydrogenization and therefore the embrittlement of steel. In hydrotreatment units, the concern is with high temperature hydrogen attack, temper embrittlement, sulfidation and corrosion/ corrosion-erosion by ammonium salt acids, NH4Cl and NH4HS. In delayed coking units the main concern is with rattcheting and thermal fatigue in the coke drum. Finally, a general solution for a corrosion and embrittlement problems in petroleum refinery involve proper materials selection, washing water, neutralizing and filming amines injection.